Optimizing Nitrogen Use Efficiency and Yield in Winter Barley: A Three-Year Study of Fertilization Systems in Southern Germany - Martin Mittermayer; Franz-Xaver Maidl; Joseph Donauer; Stefan Kimmelmann; Johannes Liebl; Kurt-Jürgen Hülsbergen (Applied Sciences)
Various fertilization systems have been developed to optimize nitrogen (N) application, yet their effectiveness remains a topic of debate in both science and practice. This study evaluates the effects of 28 N fertilization treatments on yield, quality, nitrogen use efficiency (NUE), N surplus, and economic optima in two winter barley (Hordeum vulgare L.) varieties—a multi-row and a two-row type—across a three-year field trial (2021–2023). Specifically, it compares the performance of fertilizer requirement calculations based on the German Fertilizer Application Ordinance (GFO), multispectral sensor-based fertilization systems, and fixed N input treatments. Under the trial conditions (highly productive fields without organic fertilization for decades), the GFO system consistently achieved high yields (>10 t ha−1) and NUE (up to 88%) for both barley varieties, often near economically optimal N rates and with minimal N surpluses. Sensor-based systems demonstrated promising potential for yield optimization and reducing N input; however, they did not result in significantly higher yields. Further research is needed to assess the performance of these fertilization systems under different conditions, such as sandy soils in regions with early-summer droughts or in systems involving organic fertilization.